Pupils with special educational needs in basic education schools and teachers' sickness absences - a register-linkage study - Jenni Ervasti; Mika Kivimäki; Ichiro Kawachi; S V Subramanian; Jaana Pentti; Kirsi Ahola; Tuula Oksanen; Tiina Pohjonen; Jussi Vahtera; Marianna Virtanen (Nordic Association of Occupational Safety and Health (NOROSH), 2012)
OBJECTIVES: We examined whether having a high percentage of pupils with special educational needs (SEN) in basic education schools increases the risk of sickness absence among teachers and whether this risk is dependent on the pupil-teacher ratio (PTR), an indicator of teacher resources at school. METHODS: We obtained register data on 8089 teachers working in 404 schools in 10 municipalities in Finland during the school year 2004-2005. We used multilevel multinomial regression models to examine the risk of teachers' short- and long-term sickness absence in relation to the percentage of SEN pupils and the PTR at school. We tested the equality of trends in groups with high and low PTR using PTR × SEN interaction term. RESULTS: After adjustment for teacher and school characteristics, the risk for long-term absences was higher among teachers at schools with a high percentage of SEN pupils than among teachers at schools with a low percentage of SEN pupils [odds ratio (OR) 1.5, 95% confidence interval (95% CI) 1.2-1.8). This was also the case for short-term absences (OR 1.4, 95% CI 1.2-1.7). In analyses stratified by the PTR levels, the association between the percentage of SEN pupils and long-term absences was 15% higher among teachers with a high PTR than among those with a low PTR (P for interaction=0.10). CONCLUSIONS: Teachers' sickness absenteeism seems to increase with a higher percentage of SEN pupils, especially when the PTR is high. Teacher resources at schools that have a high percentage of SEN pupils should be well maintained to ensure the health of teachers.